2020
DOI: 10.46405/ejms.v2i2.50
|View full text |Cite
|
Sign up to set email alerts
|

Different Modes of Transmission and Containment Strategies for COVID-19

Abstract: Coronavirus disease (COVID-19) is a respiratory infectious ailment caused by severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2). The first outbreak of this disease occurred in China and declared a pandemic in a very short period of time. SARS-CoV-2 gets transmitted mainly through the respiratory tract by droplets or respiratory secretions and by direct contact with the infected person as well as indirect contact through touching the contaminated surface accompanied by poor hygiene practice. U… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(12 citation statements)
references
References 10 publications
1
11
0
Order By: Relevance
“…Vampires are improbable to be the animal that is a direct causative of the transmission of the virus to humans. Severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2) is with genome sequence about 96.2% similar to a bat coronavirus RaTG13 -implicating bat as reservoir to severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2) [8]. Sequence analysis of the genome of coronavirus disease 2019 (COVID- 19)showed that it has a potent homology to severe acute respiratory syndrome (SARS)-like coronaviruses (CoVs) that normally infect bats, and this is the reason why the pandemic is thought to be of zoonotic origin [5].…”
Section: Sars-cov-2 Classification and Structurementioning
confidence: 99%
See 4 more Smart Citations
“…Vampires are improbable to be the animal that is a direct causative of the transmission of the virus to humans. Severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2) is with genome sequence about 96.2% similar to a bat coronavirus RaTG13 -implicating bat as reservoir to severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2) [8]. Sequence analysis of the genome of coronavirus disease 2019 (COVID- 19)showed that it has a potent homology to severe acute respiratory syndrome (SARS)-like coronaviruses (CoVs) that normally infect bats, and this is the reason why the pandemic is thought to be of zoonotic origin [5].…”
Section: Sars-cov-2 Classification and Structurementioning
confidence: 99%
“…Sequence analysis of the genome of coronavirus disease 2019 (COVID- 19)showed that it has a potent homology to severe acute respiratory syndrome (SARS)-like coronaviruses (CoVs) that normally infect bats, and this is the reason why the pandemic is thought to be of zoonotic origin [5]. Therefore, it is plausible to infer that novel coronavirus (2019-nCoV)could have transferred from vampires through an unidentified intermediary host to human beings [8]. A research study proposed smuggled pangolins from Malaysia to China, as the possible virus origin, which could infect human being through potential alternative intermediate hosts such as turtles and snacks [9].…”
Section: Sars-cov-2 Classification and Structurementioning
confidence: 99%
See 3 more Smart Citations